2021
DOI: 10.1108/jbsed-04-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and personal retirement planning: a socioeconomic approach

Abstract: PurposeThe purpose of this study was to investigate the effect of financial literacy on personal retirement planning in Bukavu city in the Democratic Republic of the Congo (DRC), which is a Sub-Saharan underdeveloped country with a weak pension and social security system.Design/methodology/approachThis study used a structural equation modeling and a sample of 361 public sector employees selected in Bukavu city in the DRC. The data were collected through a survey questionnaire, and the data were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…Informants of this study verbalised that lack of financial literacy forbids them from performing retirement saving. Financial literacy is important as it is a cognitive skill required to plan and save for retirement (Hershey et al, 2007;Safari et al, 2021). Past studies proved that financial knowledge is associated with private retirement savings engagement and retirement planning (Chou et al, 2014;Kumar, Shukla, & Sharma, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informants of this study verbalised that lack of financial literacy forbids them from performing retirement saving. Financial literacy is important as it is a cognitive skill required to plan and save for retirement (Hershey et al, 2007;Safari et al, 2021). Past studies proved that financial knowledge is associated with private retirement savings engagement and retirement planning (Chou et al, 2014;Kumar, Shukla, & Sharma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Van Rooij, Lusardi, & Alessie (2011) explained that financial preparedness is indicated by having proper financial planning and adequate retirement savings. Recent study has proved that individual with higher levels of financial literacy is associated with a better financial preparedness for retirement (Safari et al, 2021). According to Dulebohn (2002), financial preparedness for retirement begins with the retirement intention and savings made in the early life cycle, which would be the resources for later retirement years.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct hypotheses explain the impact of FI on economic growth. The supply-side view argues that the effect of FI on economic growth depends on how it improves capital accumulation and the general efficiency of the financial intermediation process (Beck and Frame, 2018;Safari et al, 2021;Derbali, 2021). Shittu (2012) confirms that efficiency in the financial intermediation process significantly influences economic growth (using a Nigerian dataset), and hence FI can improve economic growth.…”
Section: Jbsed 31mentioning
confidence: 99%
“…Distinct hypotheses explain the impact of FI on economic growth. The supply-side view argues that the effect of FI on economic growth depends on how it improves capital accumulation and the general efficiency of the financial intermediation process (Beck and Frame, 2018; Safari et al. , 2021; Derbali, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the study, it is concluded that financial literacy and future orientation show a positive influence on family retirement planning. Whereas Safari et al (2021) investigate the impact of financial literacy indicated by financial knowledge and computation capability on personal retirement planning amongst public sector employees in Congo. Results from the investigation revealed that both of the financial literacy components have significant impacts on personal retirement planning, indicating the significant role financial literacy plays as a determinant of personal retirement planning.…”
Section: Saving and Retirementmentioning
confidence: 99%